Improving the Resilience of Peru's Road Network to Climate Events - Rozenberg, Julie; Briceno-Garmendia, Cecilia; Lu, Xijie; Bonzanigo, Laura; Moroz, Harry (World Bank, Washington, DC, 2017)
This paper proposes a methodology to prioritize interventions in Peru's road network. A network model is built, linking the country's economic and population centers through indicative corridors, which are defined as the least-cost routes to connect origins to destinations. The network's critical links are identified by systematically simulating disruptions and calculating the costs associated with them. The network is then overlaid with natural hazard layers. The average annual losses associated with the hazard disruptions of the critical links are calculated in many scenarios, including climate change uncertainty and different impacts and reconstruction times. A robust decision-making approach is then used to select interventions that decrease hazard disruption costs.